2021
DOI: 10.1136/bcr-2020-238392
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing the vascular disruption theory of the genesis of Poland’s syndrome: a rare association of diaphragmatic eventration in a preterm infant with severe musculoskeletal defects

Abstract: A preterm female infant was admitted at birth with respiratory distress. On examination, she had an asymmetric right chest wall and ipsilateral small hand. Air entry was reduced over the right chest. A clinical diagnosis of Poland’s syndrome was made based on the hypoplasia of the right pectoral muscles, absent nipple, deformed ribs and symbrachydactyly of the ipsilateral hand. Chest X-ray suggested and ultrasound confirmed eventration of the right hemidiaphragm. ‘Subclavian artery supply disruption sequence’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The exact mechanism that leads to this syndrome is unknown. It is assumed that the spectrum of aplasia of pectoralis muscles, the athelia, and aplasia of costal ribs are consequences of interruption of the blood supply of the subscapular artery and its branches during the 6th week of development [ 4 , 9 - 10 ]. It is known that the subscapular artery or the axillary artery gives branches to key arteries that supply the thoracic wall like the medial thoracic branches, intercostal arteries, and thoracic artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism that leads to this syndrome is unknown. It is assumed that the spectrum of aplasia of pectoralis muscles, the athelia, and aplasia of costal ribs are consequences of interruption of the blood supply of the subscapular artery and its branches during the 6th week of development [ 4 , 9 - 10 ]. It is known that the subscapular artery or the axillary artery gives branches to key arteries that supply the thoracic wall like the medial thoracic branches, intercostal arteries, and thoracic artery.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are rare instances where one member of a family is identified with this condition, with no cases in the immediate or extended family. As a consequence, it is suggested that an abnormality in the vasculature formation may be the main cause of this sequence [ 4 , 9 - 10 ]. Although it is not easy to detect Poland Syndrome prenatally by ultrasound monitoring, some of its most common anatomical abnormalities (widening of coronal sutures, absence of the ossification of cranial and pubic bones, absence/hypoplasia of nasal bone, and hypoplasia of the thoracic cage) found in affected foetuses may be detected prenatally by ultrasound scan [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic anomalies in PS may involve the unilateral absence or fusion of ribs, which is often associated with scoliosis or chest wall asymmetry [31,32]. Other associated anomalies reported in some PS cases include lung herniation, dextrocardia, eventration of the diaphragm, vertebral anomalies, and urogenital abnormalities [33][34][35]. Notably, studies have also reported cutaneous webbing in areas such as the pectoral and axillary regions [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of Becker nevus syndrome has been demonstrated by Cai et al: postzygotic mutations of the ACTB gene that codes for beta-actin (6). However, a definitive pathogenesis for Poland syndrome remains to be established (1,3). In addition to the other potential 6), I respectfully propose another etiology-that Poland syndrome may also result from postzygotic mutations in beta-actin (7).…”
mentioning
confidence: 98%
“…The researchers emphasize that several hypotheses have been suggested regarding the pathogenesis of Poland syndrome (1). The vascular disruption theory (resulting from a subclavian artery supply disruption sequence) is the favored mechanism of pathogenesis (2,3). However, a Poland syndrome patient with no arterial alteration has been described (4); therefore, at least in some patients with Poland syndrome, the vascular disruption theory may not be a uniform etiology for the development of this condition.…”
mentioning
confidence: 99%